1992
DOI: 10.1080/02701367.1992.10608747
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cold Application and Modified PNF Stretching Techniques on Hip Joint Flexibility in College Males

Abstract: The purpose of the study was to determine the effects of modified Proprioceptive Neuromuscular Facilitation (PNF) flexibility techniques on hip flexion in college males and to determine if local cold application enhances the effectiveness of these techniques. Male subjects (N = 120), with an average age of 21.5 +/- 2.7 years, were randomly assigned to one of four different kinds of stretching treatments with cold or no cold application (15 per group). Range of motion (ROM) in degrees was determined following f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
8

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 11 publications
1
12
0
8
Order By: Relevance
“…Many studies have reported interesting results for hamstring shortening, pain, sports injuries, cervical spine treatment, and others, using stretching and contraction-relaxation techniques in the muscles. As in the present study, stretching of the hamstring muscles for 10 seconds, 40,41 15 seconds, 42 30 seconds, 40,43 and 60 seconds 44 and the proprioceptive neuromuscular facilitation techniques 45,46 produce a statistically significant increase in hamstring elasticity as assessed with the SLR test. For the evaluation of hamstring elasticity, other authors have used the PAT.…”
Section: Discussionmentioning
confidence: 80%
“…Many studies have reported interesting results for hamstring shortening, pain, sports injuries, cervical spine treatment, and others, using stretching and contraction-relaxation techniques in the muscles. As in the present study, stretching of the hamstring muscles for 10 seconds, 40,41 15 seconds, 42 30 seconds, 40,43 and 60 seconds 44 and the proprioceptive neuromuscular facilitation techniques 45,46 produce a statistically significant increase in hamstring elasticity as assessed with the SLR test. For the evaluation of hamstring elasticity, other authors have used the PAT.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, many researchers have reported that postisometric stretching techniques, such as MET and PNF, produce greater changes in range of motion and muscle extensibility than static or ballistic stretching, immediately following treatment (Cornelius et al, 1992;Moore and Hutton, 1980;Tanigawa, 1992;Wallin et al, 1985) and in the longer term (Handel et al, 1997;Magnusson et al, 1996a;Sady et al, 1982;Wallin et al, 1985). The exact mechanism by which increased muscle extensibility occurs is still unclear, and probably involves both neurophysiological (including changes to stretch tolerance) and mechanical factors (such as viscoelastic and plastic changes in the connective tissue elements of the muscle) (Fryer, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…on ROM, have been investigated by numerous authors. Here, a distinction has been made between alterations due to stretching that is performed repeatedly over longer periods of time (investigated by, among others, Holt et al 1970;Lucas and Koslow 1984;Sady et al 1982;Wiemann 1991) and short-term eects as measured immediately after stretching exercises (Cornelius et al 1992;Etnyre and Abraham 1986a;Moore and Hutton 1980). In these investigations,¯exibility was not measured in a uniform way.…”
Section: Introductionmentioning
confidence: 99%
“…In these investigations,¯exibility was not measured in a uniform way. Cornelius et al (1992) and Starring et al (1988) determined ROM under passive load conditions; the subjects were asked to voluntarily relax their muscles while the joint was moved for measurement by the experimentalist. In contrast, other authors performed the measurement of¯exibility actively, that is the subjects were asked to move the joint of interest to its end position by supreme eort using the muscle antagonistic to the one being stretched (Etnyre and Abraham 1986a;Holt et al 1970;Lucas and Koslow 1984;Sady et al 1982).…”
Section: Introductionmentioning
confidence: 99%